Growth and 137Cs uptake and accumulation among 56 Japanese cultivars of Brassica rapa, Brassica juncea and Brassica napus grown in a contaminated field in Fukushima: Effect of inoculation with a Bacillus pumilus strain. (June 2016) - Djedidi, Salem; Kojima, Katsuhiro; Ohkama-Ohtsu, Naoko; Bellingrath-Kimura, Sonoko Dorothea; Yokoyama, Tadashi
Abstract: Fifty six local Japanese cultivars of Brassica rapa (40 cultivars), Brassica juncea (10 cultivars) and Brassica napus (6 cultivars) were assessed for variability in growth and 137 Cs uptake and accumulation in association with a Bacillus pumilus strain. Field trial was conducted at a contaminated farmland in Nihonmatsu city, in Fukushima prefecture. Inoculation resulted in different responses of the cultivars in terms of growth and radiocesium uptake and accumulation. B . pumilus induced a significant increase in shoot dry weight in 12 cultivars that reached up to 40% in one B . rapa and three B . juncea cultivars. Differences in radiocesium uptake were observed between the cultivars of each Brassica species. Generally, inoculation resulted in a significant increase in 137 Cs uptake in 22 cultivars, while in seven cultivars it was significantly decreased. Regardless of plant cultivar and bacterial inoculation, the transfer of 137 Cs to the plant shoots (TF) varied by a factor of up to 5 and it ranged from to 0.011 to 0.054. Five inoculated cultivars, showed enhanced shoot dry weights and decreased 137 Cs accumulations, among which two B . rapa cultivars named Bitamina and Nozawana had a significantly decreased 137 Cs accumulation in their shoots. Such cultivars could be utilized to minimize the entry of radiocesium into the food chain; however, verifying the consistency of their radiocesium accumulation in other soils is strongly required. Moreover, the variations in growth and radiocesium accumulation, as influenced by Bacillus inoculation, could help selecting well grown inoculated Brassica cultivars with low radiocesium accumulation in their shoots. Graphical abstract: Highlights: Out of 56 Brassica cultivars, inoculation significantly increased shoot dry weight in 12 cultivars. Inoculation triggered a significant increase and decrease in 137 Cs uptake, respectively in 22 and 7 cultivars. Five cultivars had an enhanced shoot dry weight and decreased 137 Cs accumulation. Two B . rapa cultivars named Bitamina and Nozawana had a significantly decreased 137 Cs accumulation in their shoots. Variation in 137 Cs accumulation could help selecting Brassica cultivars with low 137 Cs accumulation.